Measuring price elasticities of demand for outbound tourism using competitiveness indices. (January 2016) - Seetaram, Neelu; Forsyth, Peter; Dwyer, Larry
Highlights: Real exchange rate (REX) is commonly used to calculate tourism price elasticity of demand. The paper discusses the limitations of REX as a proxy for prices in models of outbound tourism. It develops a price index (PCI) to calculate price elasticity of demand. PCI and REX are used in a dynamic model of Australian outbound tourism. Results confirm that compared to REX, PCI is a superior proxy for prices. Abstract: The real exchange rate (REX) has long been used as the proxy for prices in tourism demand models. However it has limitations, particularly when it comes to models of outbound tourism. As an alternative, a price competitiveness index (PCI) is developed and used as a proxy for prices in a model of outbound tourism from Australia. Results obtained show that while REX is statistically insignificant and yields a price elasticity of −0.002, PCI is significant and generates a price elasticity of −1.07. The results obtained show that PCI outperforms REX as the preferred price variable in modelling outbound demand on both theoretic and empirical grounds. Furthermore, this index can be used to monitor the inter-temporal competitiveness of a destination.